2007
DOI: 10.1590/s1020-49892007000400006
|View full text |Cite
|
Sign up to set email alerts
|

Colesterol não-HDL em escolares de 7 a 17 anos de idade em um município brasileiro

Abstract: Our findings contribute toward estimating non-HDL levels in Brazilian children and adolescents. The results also indicate that non-HDL cholesterol is a reliable and less costly method for researching the presence of dyslipidemias in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
4
7
0
4
Order By: Relevance
“…However, it is in agreement with that observed by Giuliano et al (2005) 28 in Florianópolis/SC (22.0%) and by Seki et al (2001) in Londrina/PR (20.8%) 2 . In addition, this prevalence is higher than those found by Gerber & Zielinsky, (1997) in Bento Gonçalves/RS, (10.33%) 29 and by in Itajaí/SC (4.7%) 30 .…”
Section: Discussion/conclusionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, it is in agreement with that observed by Giuliano et al (2005) 28 in Florianópolis/SC (22.0%) and by Seki et al (2001) in Londrina/PR (20.8%) 2 . In addition, this prevalence is higher than those found by Gerber & Zielinsky, (1997) in Bento Gonçalves/RS, (10.33%) 29 and by in Itajaí/SC (4.7%) 30 .…”
Section: Discussion/conclusionsupporting
confidence: 93%
“…In Brazil, there are no national epidemiological data on the prevalence of this disease that cover the entire country. However, specific studies have shown high prevalences of dyslipidemia in children and adolescents, varying between 3.1% and 46.5%, in some regions of this country [1][2][3][4][5][6][7][8][9][10] . Some studies have been performed to assess factors associated with dyslipidemia [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference was observed considering age among schoolchildren and adolescents. Other studies 14,19,21 report higher levels in schoolchildren. This data is consistent with the literature 12,22 because the drop in concentrations of TC, LDL-c, and HDL-c during puberty is attributed to the influence of sexual maturation.…”
Section: Resultsmentioning
confidence: 84%
“…Hypertriglyceridemia was defined as a fasting triglyceride level >130 mg/dl 10. The non-high-density lipoprotein (HDL)-cholesterol was calculated as the difference between total cholesterol and HDL-cholesterol 11. …”
Section: Methodsmentioning
confidence: 99%